Lessons learned from the Boran Cattle Improvement Programme at Adami Tulu and Abernossa Cattle Multiplication and Improvement Centre in Ethiopia - Tegegne, Azage (Ethiopian Society of Animal Production, 2004)
This paper describes the establishment and Development of the first indigenous cattle breed improvement endeavors in Ethiopia at the Adami Tulu and Abernossa Cattle Multiplication and Improvement Center, in the Rift Valley. It is intended to analyse and document the activities of the center and use the experiences of the center over the last three decades as a springboard for future livestock breed improvement efforts in the country. The center commenced its activities in October 1960 with an establishment herd of 351 Borana cows and 12 Borana bulls purchased from Borana and Arrero Awrajas of the then Sidamo Administration Region in southern Ethiopia. The Adami Tulu part of the ranch was the first to be established on an area of 1534 ha. The Abernossa ranch, located about 12km south west of Adami Tulu ranch, was established in 1962 on an area of :1240 ha. The major objective of this activity was to improve the Borana cattle and also to introduce modern cattle breeding and production system in the country. Activities were expanded to include a crossbreeding programme with Holstein Friesian cattle to produce in-calf crossbred heifers for distribution to farmers interested in dairy Development. Subsequently, the Borana selection and improvement programme was re-located at the Didi Tura ranch in Borana country and the center was restructured to focus on crossbred heifer production only. In its 35 years of existence, the center's activities have gone through a number of expansion and contraction, and accordingly genetic progress and retrogress in the breed improvement efforts. A major destruction and damage occurred on the ranch in 1991 when there was a change in government. Infrastructure was destroyed, records were burnt and animals were either slaughtered or looted. Subsequently, about half of the land area was given back to the local community by popular demand and the ranch was confined to the eastern part with approximately 2,000 ha. New stock (heifers) was purchased from the Borana country and restocking and improvement activities recommenced. Currently, the ranch manages about 2,000 heads of breeder cows and still produces crossbred heifers. Over the years, the ranch had made significant genetic improvement on the Borana cattle through performance evaluation and selection. However, the attempt to undertake such farfetched and long-term programme has been repeatedly hampered by the local community demanding their land rights. A participatory genetic improvement programmes that benefit local communities and the nation coupled with appropriate education and awareness creation in the community should have been designed to ensure full participation and support by the community for such long-term genetic improvement programmes.